After ENRON: empirical examination on earnings conservatism in Malaysia / Effiezal Aswadi Abdul Wahab, Mazlina Mat Zain and Maziana Madah Marzuki - Abdul Wahab, Effiezal Aswadi; Mat Zain, Mazlina; Marzuki, Maziana Madah (Universiti Teknologi MARA Cawangan Selangor, 2010)
The failure of ENRON and subsequent demise of Arthur Andersen has renewed interest in earnings and audit research. This study examines the impact of ENRON debacle on earnings conservatism in Malaysia. We hypothesised that in the period after ENRON, the auditors and managers of the firms have incentives to report more conservatively to avoid risk of litigation and to protect reputation capital. Based on a sample of 1043 firm-years over the period of 2001 and 2002, we find that, on average, firms do report more conservatively in 2002. In addition, evidence suggests that former Andersen clients report more conservatively in 2002 relatively to non-Andersen clients. Further, we document similar results for firms switching to from another Big 4 to another Big 4 auditing firm in 2002. Finally, we discover firms that did not switch in 2002 do report more conservatively in 2002. We conclude that the ENRON debacle have a profound impact on firms to report more timely earnings. JEL classification: M42